Iron oxyfluorides as lithium-free cathode materials for solid-state Li metal batteries. Issue 35 (1st September 2017) - Wang, Li-Ping; Wang, Tai-Shan; Zhang, Xu-Dong; Liang, Jia-Yan; Jiang, Li; Yin, Ya-Xia; Guo, Yu-Guo; Wang, Chun-Ru
Abstract : High energy density storage systems can be achieved by utilizing a lithium metal anode in solid-state Li secondary batteries. Abstract : High energy density storage systems can be achieved by utilizing a lithium metal anode in solid-state Li secondary batteries. Herein, we report for the first time the use of a lithium-free cathode coupled with lithium metal for solid-state Li metal batteries. This lithium-free cathode composed of iron oxyfluoride (FeOF) nanorods can not only reduce the consumption of lithium resources, but also provide a good electrochemical performance. After being encapsulated by a highly conductive poly(3, 4-ethylenedioxythiophene) (PEDOT) nanolayer, the coated FeOF nanorods exhibit a superior cycling stability ( ca. 75% capacity retention after 200 cycles at 100 mA g −1 ) at 60 °C in a PEA solid electrolyte. This performance demonstrates the great potential of lithium-free cathodes for application in solid-state Li metal batteries.